Antihypertrophic Memory After Regression of Exercise-Induced Physiological Myocardial Hypertrophy Is Mediated by the Long Noncoding RNA Mhrt779. Issue 23 (24th March 2021) - Lin, Hairuo; Zhu, Yingqi; Zheng, Cankun; Hu, Donghong; Ma, Siyuan; Chen, Lin; Wang, Qiancheng; Chen, Zhenhuan; Xie, Jiahe; Yan, Yi; Huang, Xiaobo; Liao, Wangjun; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Exercise can induce physiological myocardial hypertrophy (PMH), and former athletes can live 5 to 6 years longer than nonathletic controls, suggesting a benefit after regression of PMH. We previously reported that regression of pathological myocardial hypertrophy has antihypertrophic effects. Accordingly, we hypothesized that antihypertrophic memory exists even after PMH has regressed, increasing myocardial resistance to subsequent pathological hypertrophic stress. Methods: C57BL/6 mice were submitted to 21 days of swimming training to develop PMH. After termination of exercise, PMH regressed within 1 week. PMH regression mice (exercise hypertrophic preconditioning [EHP] group) and sedentary mice (control group) then underwent transverse aortic constriction or a sham operation for 4 weeks. Cardiac remodeling and function were evaluated with echocardiography, invasive left ventricular hemodynamic measurement, and histological analysis. LncRNA sequencing, chromatin immunoprecipitation assay, and comprehensive identification of RNA-binding proteins by mass spectrometry and Western blot were used to investigate the role of Mhrt779 involved in the antihypertrophic effect induced by EHP. Results: At 1 and 4 weeks after transverse aortic constriction, the EHP group showed less increase in myocardial hypertrophy and lower expression of the Nppa and Myh7 genes than the sedentary group. At 4 weeks after transverse aortic constriction, EHP mice had less pulmonary congestion, smaller left ventricular dimensions and end-diastolic pressure, and a larger left ventricular ejection fraction and maximum pressure change rate than sedentary mice. Quantitative polymerase chain reaction revealed that the long noncoding myosin heavy chain–associated RNA transcript Mhrt779 was one of the markedly upregulated lncRNAs in the EHP group. Silencing of Mhrt779 attenuated the antihypertrophic effect of EHP in mice with transverse aortic constriction and in cultured cardiomyocytes treated with angiotensin II, and overexpression enhanced the antihypertrophic effect. Using chromatin immunoprecipitation assay and quantitative polymerase chain reaction, we found that EHP increased histone 3 trimethylation (H3K4me3 and H3K36me3) at the a4 promoter of Mhrt779 . Comprehensive identification of RNA-binding proteins by mass spectrometry and Western blot showed that Mhrt779 can bind SWI/SNF related, matrix associated, actin dependent regulator of chromatin, subfamily a, member 4 (Brg1) to inhibit the activation of the histone deacetylase 2 (Hdac2)/phosphorylated serine/threonine kinase (Akt)/phosphorylated glycogen synthase kinase 3β(p-GSK3β) pathway induced by pressure overload. Conclusions: Myocardial hypertrophy preconditioning evoked by exercise increases resistance to pathological stress via an antihypertrophic effect mediated by a signal pathway of Mhrt779 /Brg1/Hdac2/p-Akt/p-GSK3β